2016
DOI: 10.2147/copd.s107396
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory mechanism of <em>Cordyceps sinensis</em> on cigarette smoke extract-induced senescence in human bronchial epithelial cells

Abstract: ObjectivesCellular senescence is a state of irreversible growth arrest induced either by telomere shortening (replicative senescence) or stress. The bronchial epithelial cell is often injured by inhaled toxic substances, such as cigarette smoke. In the present study, we investigated whether exposure to cigarette smoke extract (CSE) induces senescence of bronchial epithelial cells; and Cordyceps sinensis mechanism of inhibition of CSE-induced cellular senescence.MethodsHuman bronchial epithelial cells (16HBE ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…LTB4 is a potent neutrophil chemoattractant and activator and a very important regulator of inflammation in vivo [26]. LTB4 can activate and aggregate a variety of inflammatory and immune effector cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…LTB4 is a potent neutrophil chemoattractant and activator and a very important regulator of inflammation in vivo [26]. LTB4 can activate and aggregate a variety of inflammatory and immune effector cells [27].…”
Section: Discussionmentioning
confidence: 99%
“… 17 19 Numerous studies have shown that the C. sinensis extracts have a therapeutic effect on patients with COPD, including improvement of symptoms, quantity of life, and lung function. 20 , 21 A mechanistic study suggests that the C. sinensis extract inhibits the senescence induced by CSE in human bronchial epithelial cells via the ROS/PI3K/AKT/mTOR signaling pathway. 20 …”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 A mechanistic study suggests that the C. sinensis extract inhibits the senescence induced by CSE in human bronchial epithelial cells via the ROS/PI3K/AKT/mTOR signaling pathway. 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that this medicine may also have a protective effect against lung diseases ( 23 , 24 ). In a previous study conducted by the present research group, it was revealed that C. sinensis was able to significantly inhibit senescence via the reactive oxygen species and phosphoinositide 3-kinase/AKT/mechanistic target of rapamycin signaling pathways in cigarette smoke extract (CSE)-induced 16 human bronchial epithelial cells (HBEs) ( 25 ). Previous reports have suggested that C. sinensis may have anti-fibrotic effects ( 24 , 26 , 27 ).…”
Section: Introductionmentioning
confidence: 96%